2014
DOI: 10.1186/2052-4374-26-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimated rate of agricultural injury: the Korean Farmers’ Occupational Disease and Injury Survey

Abstract: ObjectivesThis study estimated the rate of agricultural injury using a nationwide survey and identified factors associated with these injuries.MethodsThe first Korean Farmers’ Occupational Disease and Injury Survey (KFODIS) was conducted by the Rural Development Administration in 2009. Data from 9,630 adults were collected through a household survey about agricultural injuries suffered in 2008. We estimated the injury rates among those whose injury required an absence of more than 4 days. Logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…Furthermore, the possibility of an ocular injury occurring was greater for individuals working more hours (OR 2.09, 95% CI: 1.08-4.03) on cocoa farms, similar to that reported by other authors in agricultural health studies 26,40,41,42 . An interesting finding in this study is the fact that participants who had poor perception of near vision had a higher probability (OR 1.26, 95% CI: 1.05 -1.52) of sustaining ocular injuries.…”
supporting
confidence: 76%
“…Furthermore, the possibility of an ocular injury occurring was greater for individuals working more hours (OR 2.09, 95% CI: 1.08-4.03) on cocoa farms, similar to that reported by other authors in agricultural health studies 26,40,41,42 . An interesting finding in this study is the fact that participants who had poor perception of near vision had a higher probability (OR 1.26, 95% CI: 1.05 -1.52) of sustaining ocular injuries.…”
supporting
confidence: 76%
“…This finding is in agreement with the literature, which indicates risk two to three times greater for males 11,27,28,31 , although it has been demonstrated that women handling tools and animals are 49% more at risk in Colorado 32 . Diverse studies have found higher risk among individuals aged over 50 years 6,7,11,31,33 . This fact was not found in tobacco farming and perhaps this was influenced by the division of labour according to age, whereby more arduous and risky jobs are delegated to the younger.…”
Section: Discussionmentioning
confidence: 99%
“…Although no association was found between accidents and number of hours worked, which is in agreement with another study conducted in the same region of Brazil 16 , other studies have shown that longer daily working hours, above ten hours a day, increased the risk of accidents by two to three times among workers in the United States 8,21,33 , China 34 . Australia 35 and Korea 7 . Males have longer working hours and thus the association between daily working hours and accidents lost significance after adjustment for sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As confirmed by a recent report from the European Agency for Safety and Health at Work (EU-OSHA), fatalities in agriculture are three times higher than the average [6]. In non-European countries, this situation is very similar, including in the United States [7], Canada [8], Australia [9], and Korea [10].…”
Section: Introductionmentioning
confidence: 92%